Performance Comparison of Crossflow Turbine Configuration Upper Blade Convex and Curvature by Computational Method - Dendy Adanta; Dewi Puspita Sari; Imam Syofii; Aji Putro Prakoso; Muhammad Amsal Ade Saputra; Ismail Thamrin (Civil Engineering Journal, 2023)
A pico-hydro-type crossflow turbine (CFT) with an off-grid system configuration is a suitable option to increase the electrification ratio in remote or rural areas because it has a simple shape and can be applied in run-of-river conditions. Yet, a comprehensive study is necessary for the CFT to be applied to run-of-river conditions (low head and extreme fluctuation discharge), since this is categorized as an impulse turbine. One solution to optimize the CFT’s performance in this context is to increase the lift force. Hence, this study investigated the effect of the upper blade of the CFT with convex and curved configurations using the computational fluid dynamics (CFD) method. The CFD transient approach uses a moving mesh feature, and the solver is pressure-based in low-head conditions (5 m pressure). The CFD results and analysis of variance (ANOVA) calculation results from this study reveal that the upper CFT affects the performance of the turbine. The relationship of the CFT performance with the rotation and specific speed is parabolic. The express empirical law relation for performance to rotation is a four-order polynomial, and for performance to a specific speed, a three-order polynomial. Based on empirical laws, a CFT with a convex blade is recommended for conditions with low head and extreme fluctuation discharge since it has a wider range of specific speeds than a curved blade, propeller, or Kaplan, Pelton, or Francis turbine. Doi: 10.28991/CEJ-2023-09-01-012 Full Text: PDF